2005
DOI: 10.1111/j.1471-6402.2005.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Objectification, Risk Taking, and Self-Harm in College Women

Abstract: Objectification theory proposes that the objectification of women's bodies causes women to self-objectify, adopting an outsider's view of themselves. Engaging in a high amount of self-objectification is thought to place women at increased risk for mental health problems such as body dissatisfaction and depression. It was hypothesized that self-objectification would contribute to negative body regard and depression, which would increase participation in risk-taking and selfharmful behaviors. Structural equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
94
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 51 publications
14
94
0
2
Order By: Relevance
“…Mild aspects of dissociation may also contribute to some of the bodily disturbances observed among individuals with NSSI and ED. Some researchers acknowledge that a negative attitude toward the body and disconnection from bodily experiences (e.g., alexithymia) may be a critical component in both NSSI and ED (Muehlenkamp, Swanson & Braush, 2005;Walsh, 2012) because dissatisfaction may promote devaluing of the body alongside views of the body as a hated object, which make it easier to harm. The increased rates of body dissatisfaction among those who engage in NSSI are even notable within ED patients, who conceptually already suffer from high levels of body dissatisfaction .…”
Section: Proximal Risk Factorsmentioning
confidence: 97%
“…Mild aspects of dissociation may also contribute to some of the bodily disturbances observed among individuals with NSSI and ED. Some researchers acknowledge that a negative attitude toward the body and disconnection from bodily experiences (e.g., alexithymia) may be a critical component in both NSSI and ED (Muehlenkamp, Swanson & Braush, 2005;Walsh, 2012) because dissatisfaction may promote devaluing of the body alongside views of the body as a hated object, which make it easier to harm. The increased rates of body dissatisfaction among those who engage in NSSI are even notable within ED patients, who conceptually already suffer from high levels of body dissatisfaction .…”
Section: Proximal Risk Factorsmentioning
confidence: 97%
“…Empirical studies have demonstrated that both interpersonal forms (Hill & Fischer, 2007;Kozee & Tylka, 2006; Running head: OBJECTIFICATION THEORY AND COSMETIC SURGERY 5 Kozee, Tylka, Augustus-Horvath, & Denchik, 2007;Moradi, Dirks, & Matteson, 2005) and media forms (Harper & Tiggemann, 2008;Morry & Staska, 2001) of sexual objectification contribute to self-objectification. Moreover, there is strong evidence from studies of women across North America, Australia, and the U.K. indicating that self-objectification, and the concomitant self-surveillance, exact significant costs on womenÕs subjective well-being (Breines, Crocker, & Garcia, 2008;Fairchild & Rudman, 2008) and cognitive performance (Fredrickson, Roberts, Noll, Quinn, & Twenge, 1998;Quinn, Kallen, Twenge, & Fredrickson, 2006), with a greater prevalence of self-harming behavior (Harell, Fredrickson, Pomerleau, Nolen-Hoeksema, 2006;Muehlenkamp, Swanson, & Brausch, 2005) and a disproportionately higher rate of mental health risks, including depression (Grabe, Hyde, & Lindberg, 2007;Tiggemann & Kuring, 2004), disordered eating (Calogero, Davis, & Thompson, 2005;Tylka & Hill, 2004), and sexual dysfunction (Calogero & Thompson, 2009b;Steer & Tiggemann, 2008). In particular, researchers have identified body shameÑthe degree to which women feel ashamed of their bodies when they perceive them as falling short of feminine beauty ideals (McKinley & Hyde, 1996)Ñas a key negative emotional consequence of self-objectification (Fredrickson & Roberts, 1997;Moradi & Huang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is strong evidence from studies of women across North America, Australia, and the United Kingdom that higher self-objectification, and the concomitant self-surveillance, may exact significant costs on womenÕs subjective well-being (Breines, Crocker, & Garcia, 2008;Fairchild & Rudman, 2008) and cognitive performance (Fredrickson, Roberts, Noll, Quinn, & Twenge, 1998;Quinn, Kallen, Twenge, & Fredrickson, 2006). These costs include self-harming behavior (Harrell, Fredrickson, Pomerleau, Nolen-Hoeksema, 2006;Muehlenkamp, Swanson, & Brausch, 2005), cosmetic surgical procedures (Calogero, Pina, Park, & Rahemtulla, 2010), and a higher rate of mental health risks, including depression (Grabe, Hyde, & Lindberg, 2007;Tiggemann & Kuring, 2004), disordered eating (Calogero, Davis, & Thompson, 2005;Tylka & Hill, 2004), and poor sexual functioning (Calogero & Thompson, 2009;Steer & Tiggemann, 2008).…”
Section: Self-objectification and Related Consequencesmentioning
confidence: 99%